Transition, structural divergence, and performance: Eastern Europe and the former Soviet Union over 2000-2007 - Giovanni Andrea Cornia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
During the socialist era the communist regime attempted to reduce development differentials among states and social classes. In contrast, during the last 20 years, the economies in transition experienced considerable divergence in the economic, social, demographic and political areas. As a result, these countries can now be grouped into four structurally different clusters alternatively dependent on manufactured exports, high- and low-tech services, commodities exports, and migrant remittances. Between 2000 and 2007, the cluster with the fastest growth was not that which most reformed its economy and institutions, but that of commodity exporters where, however, life expectancy improved far less than in other clusters.
Keywords: P2; P21; P36; O4; 330; structural transformation; divergence; performance; country clusters